Effective application of reverse circulation structure against bank erosion of Vu Gia river at Dai Cuong commune, Quang Nam province - Giap, Nguyen Dang; Son, Hoang Thanh (Vietnam Journal of Earth Sciences, 2012)
Vietnam has an abundant river system with big residential areas and important economic - cultural constructions along the banks. However, dynamical processes are causing erosion of river bank, especially at curve sections of the rivers. Task of preventing river erosion and protecting river’s constructions are always the meaningfully and practically major mission of science and technology. On some river sections, the attic and soldering embankments are usually ineffective in river bank erosion, especially when flows are very strong and/or floods. Application of the reverse circulation structures to protect concave banks is a new river treatment used as a pilot application in Vietnam. As a result, this method has surmounted weak points of usual  embankments and protected river bank effectively, raising the level of deposit quickly just after a high water season.